Maternal micronutrients can modify colonic mucosal microbiota maturation in murine offspring - Nagy-Szakal, Dorottya (Landes Bioscience, 2012)
Epidemiologic data suggest that early nutritional exposures may inflict persistent changes in the developing mammalian “super-organism” (i.e., the host and its residing microbiota). Such persistent modifications could predispose young adults to inflammatory bowel diseases (IBD). We recently observed that the dietary supplementation of four micronutrients to dams augmented colitis susceptibility in murine offspring in association with mucosal microbiota composition changes. In this study the effects of the four micronutrients on the microbiota of dams and female mice was examined. Additionally, age dependent microbiota composition shifts during pediatric development were delineated from the previous offspring data sets. Maternal and adult female microbiota did not separate secondary to the nutritional intervention. Significant microbiota composition changes occurred from postnatal day 30 (P30) to P90 at the level of 1 phylum and 15 genera. Most of these changes were absent or opposite in the maternally supplemented offspring. Nutritionally induced alterations in mucosal microbiota maturation may be contributors to colitis susceptibility in mammals.